Antibody‐ and macrophage‐mediated segmental demyelination in chronic inflammatory demyelinating polyneuropathy: clinical, electrophysiological, immunological and pathological correlates. (22nd December 2019) - Vallat, J.‐M.; Mathis, S.; Vegezzi, E.; Richard, L.; Duchesne, M.; Gallouedec, G.; Corcia, P.; Magy, L.; Uncini, A.; Devaux, J.
Abstract : Background and purpose: Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a heterogeneous autoimmune disorder critically lacking diagnostic biomarkers. Autoantibodies to nodal and paranodal components have recently been described in a small subset of patients. Here, the diagnostic value of immune reactivity toward the myelin compartment was investigated. Methods: Ninety‐four French CIDP patients were retrospectively studied. The reactivity toward the peripheral nerve was investigated. Sural nerve biopsies were examined by electron microscopy and immunofluorescence. Results: Twenty‐one patients (22%) and three patients (3%) presented with a strong immunoglobulin G or immunoglobulin M reactivity respectively against the myelin compartment. The clinical, electrophysiological and morphological features were examined in nine of these patients for whom sural nerve biopsies were available. Seven patients were electrodiagnosed with definite CIDP, one with possible CIDP and one was unclassifiable but sural nerve biopsy argued for CIDP diagnosis. Electron microscopy of sural nerve biopsies demonstrated the presence of macrophage‐mediated demyelination restricted to the internode in all nine patients. Immunolabelling for voltage‐gated sodium channels, myelin and axonal markers confirmed the presence of segmental demyelination and of remyelination. The nodal and paranodal regions, however, were unaffected in these patients. Nerve conduction studies corroborated the multifocal and segmental profile, and seven patients showed increased duration of proximal (1.5–5.1 times) and/or distal (1.2–3.4 times) compound muscle action potential in at least two nerves. Conclusion: Antibody‐ and macrophage‐mediated demyelination appears responsible for conduction alterations in CIDP patients and nerve immunostaining assays may serve as a supportive diagnostic biomarker.